Exploring the Relationship between Body Mass Index and Anxiety Status Among Ahlia University Students - Tantawy, Sayed; Karamat, Nada Ikram; Al Gannas, Rana Sulaiman; Khadem, Sara Abdulrahman; Kamel, Dalia M. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Mood disorders such as generalized anxiety disorder (GAD), obsessive-compulsive disorders, and other mental disorders could be due to obesity which is a prevalent condition among majority of population nowadays, whereas changes in anxiety level of individuals are also thought to have an influence on body mass index (BMI). AIM: The objective of the study was to investigate the relationship between BMI and anxiety status among Ahlia University students. METHODS: A total of 80 male and female students from different colleges of Ahlia University were included in our study. Their ages ranged between 18 and 25 years old with different BMI. The students were asked to fill a (GAD 7 scale) questionnaire related to anxiety level; their BMI was calculated. RESULTS: There was a significant relationship between BMI and anxiety status (negative correlation) (p < 0.019). CONCLUSIONS: We concluded that BMI is inversely proportional to anxiety level, the reduction in BMI level is linked with elevated anxiety level and vice versa.